ANALISIS PENGELOLAAN KEUANGAN PADA USAHA MIKRO: Studi Kasus Pada Rumah Makan Ampera Di Kelurahan Simpang Baru Kota Pekanbaru - Kristina Sihotang; Mariaty Ibrahim (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
Micro businesses play an important role in increasing and equalizing community income so as to realize national stability, because this business can expand employment opportunities. However, micro businesses are not free from various obstacles, especially obstacles in the management of business finances that are not yet effective. Many micro businesses have not been able to implement 4 indicators of financial management, namely planning, recording, reporting and control. This study aims to determine the Financial Management of Micro Business Ampera Restaurant in Simpang Baru Village, Pekanbaru City. This type of research is qualitative with a descriptive approach. Data sources were obtained through observation, interviews and documentation involving 10 informants. The results of the study indicate that Financial Management at Ampera Restaurant in Simpang Baru Village, Pekanbaru City is not optimal. Of the 4 indicators of financial management, only the planning indicator can be said to be good. This is due to the lack of knowledge and limited human resources in recording, reporting and controlling. The results of this study are expected to provide useful information to improve financial management for micro-entrepreneurs.